Perubahan Tutupan Lahan Kota Ambon Tahun 2015, 2019 dan 2023 - Philia Christi Latue; Juan Steiven Imanuel Septory; Heinrich Rakuasa (Universitas Lambung Mangkurat, 2023)
Population growth and the Maluku Province economy which is concentrated in Ambon City make the need for land resources to increase, while the existence of land that is relatively constant will result in a decrease in the carrying capacity of the environment and result in environmental degradation and damage. This study aims to determine spatially changes in land cover in Ambon City in 2015, 2019 and 2023. SPOT 6 imagery data for 2015, 2019 and 2023 were used in this study to analyze land cover changes that have occurred. The process of georeferencing, digitizing on screen and land cover classification is carried out by Arc GIS software to produce a land cover map. The results showed that the cover of built-up land and open land continues to increase in area every year in line with population growth and the high demand for land in Ambon City.